Psychological Adjustment of Counselling Psychologists in Nigeria During Covid-19 Pandemic Peak Period: Correlate of Self-Efficacy, Emotional Maturity and Religiosity - Ofole, Ndidi Mercy (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This examined investigated the relationship between counselling self-efficacy, emotional maturity and religiosity are correlated with psychological adjustment of Nigerian counselling psychologists during the peak of the covid 19 pandemic. Cross sectional design was adopted to sample three hundred and fifty-three (male=47.9 % female=52.1 %) with age range of 22-54 years from Counselling Psychologists in Nigeria.  Web-based survey was utilized as platform to distribute the google link containing the questionnaire.  Product Moment Correlation (PPMC), Multiple Regression Analysis (MRA) and t-test for independent samples were used as statistical tools and the margin of error for testing the hypotheses was .0.05. The result showed that there was significant difference in psychological adjustment of respondents based on gender (t (351) = 2.141, p<.05). The females were more psychologically adjusted (=34.86) than their male counterparts (=32.73). Further, psychological adjustment was positively correlated with counselling self-efficacy r=(df=351) = .519 P < 0.05), emotional maturity; r (df=351) =.557 P < 0.05) and religiosity (r (df=351) = .397 P < 0.05).  Regression analysis indicates that the three variables can jointly account for 38 % of variance in predicting the psychological adjustment of counselling psychologists in Nigeria. Counselling self-efficacy was most potent (β =.281, p<0.05). The result provided evidence to suggest that the factors considered in this contributed positively to the psychological adjustment of counselling psychologists during the peak period of covid 19 in Nigeria. Counselling psychologists should be screened in order to identify Practioners who are deficit in these non-cognitive skills.